Čija kriza? - Grubački, Isidora (Prispevki za novejšo zgodovino, 2022)
In 1929, the central feminist organization in the interwar Kingdom of Serbs, Croats, and Slovenes / Yugoslavia Alijansa ženskih pokreta (Women's Movements' Alliance) removed the demand for women's suffrage rights from its program. By analyzing and carefully contextualizing articles published in the central Yugoslav feminist magazine Ženski pokret (Belgrade, 1920-1938), the article addresses a specific gap in the historiography of women's movements and feminisms in interwar Yugoslavia, and argues that the removal of this demand from the feminists' program was not only a direct consequence of the Royal dictatorship, but also a reflection of a broader disillusionment with parliamentary and party politics in interwar Yugoslavia. More broadly, the article addresses the narrative of the “crisis of feminism”, and demonstrates that this is not a sufficiently satisfactory explanation for the transformation of feminism in the late 1920s and early 1930s. Furthermore, the article contributes to the historiography of the political history of feminisms, and acknowledges the intertwining history of the Yugoslav feminist movement with parliamentary and party politics. Methodologically, it follows the recent approaches to the history of political thought in East Central Europe, and provides new insights into the political thought of the feminists from the AŽP, and particularly their leader Alojzija Štebi’s “political vocabulary” and her understanding of political neutrality, moral crisis of political life, and small-scale work.
Keywords: feminizem; Jugoslavija; Kraljevina SHS; politična zgodovina; politični diskurz; politika; volilna pravica